Constraints and priorities in agriculture from the technological perspective in Latinoamerica and the Caribbean - Alarcón, Enrique (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2021)
This document has been prepared on information drawn from several sources, including documents and fora and workshops held in different parts of Latin America and the Caribbean (LAC) to address the problems and priorities of the region regarding agriculture and the rural milieu, from the perspective of technological development and in the context of the work carried out under FORAGRO.